Moneta rivolzione e filosofia dell'avvenire: Nietzsche e la politica accelerazionista in Deleuze, Foucault, Guattari, Klossowski (Obsolete Capitalism Free Press, 2016)
A book of political philosophy designed for Obsolete Capitalism Free Press. The authors investigate some grey areas of accelerationist politics through the lens of the most visionary philosophers: Deleuze, Foucault, Guattari and Klossowski.'We live projected into an era of instant communication and total monitoring. New forms of control appear unstoppable. The museum of ideologies is filled with dying concepts such as Capitalism, Neoliberalism, Marxism, Keynesianism. Today the system modulates the various forces that innervate our world: Money, Research, Control, Information, Circuit are old names which through acceleration produce a new power.''The higher the immanence of the Market, the greater the likelihood that interruptions, viruses, leaks, bifurcations, invisibility will replace conflicts.''This antology begins with the analysis of a fragment written by Friedrich Nietzsche and nestled in a crucial passage of Deleuze and Guattaris Anti-Oedipus. This fragment of thought is the point of departure of a journey throughout which, peraphs, a different kind of accelerationism can be advanced. One expressed through a new politics of bodies, waves and forces whose relationship with technology is mediated by experimantation, creation and critique, trial and error, do-it-yourself and do-it-together.'
Keywords: Nietzsche, Friedrich Wilhelm -- 1844-1900; Deleuze, Gilles -- 1925-1995; Foucault, Michel -- 1926-1984; Guattari, Félix -- 1930-1992; Klossowski, Pierre